Des pieds de moutons dans la citerne du sanctuaire de Corent (Veyre-Monton, Puy-de-Dôme) : rejet détritique ou dépôt rituel ? - Sylvain Foucras (Revue Archéologique du Centre de la France)
At the turn of the second and third century AD, a spectacular collection of more than 120 sheep hooves was thrown into the cistern located inside the sanctuary of Corent. Everything seems to show that once this act was done, the tank was quickly filled in, and then sealed by an impressive limestone slab. The zooarchaeological study reveals that despite their anarchic position at the bottom of the structure, these legs are divided equally between forelimb and hindlimb and between left and right. So it must be the comprehensive rejection of the lower legs of thirty sheep, with other anatomical parts discarded.This unusual ensemble seems to evoke rejects linked to butchering and cottage industry.Yet its disposal within the confines of a sacred place activity is not common.Simple rejection detrital or ritual deposit, the same choice of sheep, an animal that plays a central role in Arvernian ritual practices, raises questions about the purpose of this whole cult.